Subcellular expression of aquaporin-4 in substantia nigra of normal and MPTP-treated mice. (17th September 2017) - Prydz, Agnete; Stahl, Katja; Puchades, Maja; Davarpaneh, Nina; Nadeem, Maria; Ottersen, Ole Petter; Gundersen, Vidar; Amiry-Moghaddam, Mahmood
Highlights: This is the first thorough analysis of the distribution of aquaporin-4 (AQP4) in the substantia nigra (SN). Perivascular density of AQP4 in SN is 70% higher than in the neocortex of healthy mice. Expression of AQP4 in the astrocyte processes in neuropil is 120% higher than in neocortex of healthy mice. Systemic treatment with MPTP leads to a significant increase in AQP4 expression in SN. Abstract: Aquaporin-4 (AQP4) is the predominant water channel in mammalian CNS where it is localized at the perivascular astrocytic foot processes abutting brain microvessels. Several lines of evidence suggest that AQP4 is involved in important homeostatic functions and that mislocalization of the perivascular pool of AQP4 is implicated in several different brain disorders. A recent study suggests that the differential susceptibility of midbrain dopaminergic neurons to the parkinsonogenic toxin 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) depends on the expression of AQP4. Further, MRI studies of patients with Parkinson's disease (PD) point to an excessive water accumulation in the substantia nigra (SN). This prompted us to investigate the cellular and subcellular distribution of AQP4 in mouse SN using immunofluorescence and quantitative immunogold cytochemistry. Compared with neocortex, SN exhibits a higher concentration of AQP4. Specifically, judged by electron microscopic immunogold analysis, the perivascular density of AQP4 in SN exceeds by 70% the perivascular density of AQP4 in the neocortex. An even larger difference in AQP4 labeling was found for astrocytic processes in the neuropil. Treatment with MPTP further increased (by >30%) the perivascular AQP4 density in SN, but also increased AQP4 labeling in the neocortex. Our data indicate that the perivascular AQP4 pool in SN is high in normal animals and even higher after treatment with MPTP. This would leave the SN more prone to water accumulation and supports the idea that AQP4 could be involved in the pathogenesis of PD.